PERANCANGAN SISTEM INFORMASI PENJUALAN PAKAIAN BERBASIS WEB (E-COMMERCE) PADA TOKO ADSIDEA FASHION - Teuku Fadjar Shadek; Darpi Darpi; Sawitri Nurhayati; Vira Mustika (Journal of Innovation And Future Technology, 2025)
AdsIdea is a business engaged in the sale of women's clothing. Currently, the sales system used is still manual. Transaction records are kept in a basic logbook, which often leads to issues such as input errors, lost or damaged data, and even duplicate entries due to human error during the recording process. This research aims to design a web-based clothing sales system (E-Commerce) to improve the effectiveness and efficiency of sales activities at AdsIdea Fashion. Data collection techniques used include observation, interviews, and literature review. The system development methodology applied in this study is the Waterfall model. The system design is supported by the use of UML (Unified Modeling Language) tools, such as Use Case Diagram, Class Diagram, Activity Diagram, and Sequence Diagram. The system is implemented using the PHP (Hypertext Preprocessor) programming language with MySQL as the database management system. The outcome of this research is a web-based E-Commerce information system that enables AdsIdea Fashion to streamline product information access for customers, accelerate centralized data processing through an integrated database, and support online marketing and promotional activities more effectively.